Energy prices and economic performance in South Africa: an ARDL bounds testing approach - Siyakudumisa Takentsi; Kin Sibanda; Yiseyon-Sunday Hosu (Cogent Economics & Finance, 2022)
This paper empirically investigates the causal relationship between energy prices and economic performance in South Africa by employing the auto-regressive distributed lag (ARDL) bounds test technique for the period 1994 to 2019. The empirical evidence that was reviewed used a different methodology and covered different periods, particularly in the South African context. While previous studies investigated energy prices by examining oil or electricity prices separately, this study combined these prices in the regression model. The ARDL model is capable of detecting hidden cointegration relationships and works even in series that are integrated of different orders. The study established a long-run relationship between the variables. The findings revealed that electricity prices have a significant negative impact on economic growth in the long and short run, while crude oil prices show a significant positive linkage with economic growth in the long and short run. The Granger causality analysis did not establish a causal relationship between energy prices and economic growth in South Africa. However, it pointed to unidirectional causality from both labour productivity and gross fixed capital formation to economic growth. It is thus recommended that the government should take steps to mitigate the effects of high electricity prices on economic growth in South Africa.
Keywords: 330; energy prices; economic performance; Granger causality; ARDL; South Africa